2001
DOI: 10.1074/jbc.m009424200
|View full text |Cite
|
Sign up to set email alerts
|

Gaf-1, a γ-SNAP-binding Protein Associated with the Mitochondria

Abstract: The role of ␣/␤-SNAP (Soluble NSF Attachment Protein) in vesicular trafficking is well established; however, the function of the ubiquitously expressed ␥-SNAP remains unclear. To further characterize the cellular role of this enigmatic protein, a two-hybrid screen was used to identify new, ␥-SNAP-binding proteins and to uncover potentially novel functions for ␥-SNAP. One such SNAP-binding protein, termed Gaf-1 (␥-SNAP associate factor-1) specifically binds ␥-but not ␣-SNAP. The full-length Gaf-1 (75 kDa) is ub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 57 publications
(24 reference statements)
1
20
0
Order By: Relevance
“…Interestingly, FIP3 and FIP4, members of the class II Rab11-FIP proteins, interact with Exo70 within the exocyst complex, and this is proposed to couple Rab11-positive vesicles to the cleavage furrow during cytokinesis (Fielding et al, 2005). Furthermore, Rip11 has been reported to interact with ␥SNAP, a component of the SNARE complex (Chen et al, 2001). These observations are of significant interest because Rab proteins are well established to play an important modulatory role in the SNARE-mediated fusion complex that controls several homotypic and heterotypic membrane fusion events (Stamnes et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, FIP3 and FIP4, members of the class II Rab11-FIP proteins, interact with Exo70 within the exocyst complex, and this is proposed to couple Rab11-positive vesicles to the cleavage furrow during cytokinesis (Fielding et al, 2005). Furthermore, Rip11 has been reported to interact with ␥SNAP, a component of the SNARE complex (Chen et al, 2001). These observations are of significant interest because Rab proteins are well established to play an important modulatory role in the SNARE-mediated fusion complex that controls several homotypic and heterotypic membrane fusion events (Stamnes et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the recombinant full-length Rip11 binds poorly to Rab11a in pulldown and yeast two-hybrid assays as compared with full-length endogenous Rip11 from cellular TX-100 extracts (data not shown). Furthermore, it has been previously shown that Rip11 can also interact with ␥SNAP and cytoskeleton (13,24). Thus, the interactions of Rips and Eferin with different factors could be used as a means of differentially regulating Rab11/25 binding.…”
Section: Fig 3 Identification Of the Rbd11 Conserved In Rip Andmentioning
confidence: 99%
“…In addition to NSF, which we have previously reported , several SNARE proteins, SNARE-associated proteins (Sly1/Sec1-family domain containing proteins 1 and 2, SCFD1 and SCFD2, respectively), α-SNAP and other membranetrafficking-related proteins -including clathrin heavy chain and phosphoinositide phosphatase Sac1 -were detected. Among these, we decided to focus on SNAREs because their interactions with γ-SNAP have remained poorly characterized (Chen et al, 2001;Hong, 2005;Tani et al, 2003).…”
Section: γ-Snap Preferentially Binds To Endosomal Snaresmentioning
confidence: 99%
“…In contrast to the considerable contribution of α-SNAP and β-SNAP to SNARE complexes in membrane trafficking events, the biochemical and cellular functions of γ-SNAP remain poorly understood. Yeast twohybrid screening experiments have revealed that γ-SNAP interacts with γ-SNAP-associated factor-1 [Gaf-1; also known as Rab11-interacting protein (Rip11) and Rab11-family interacting protein 5 (FIP5)], γ-tubulin and NSF (Chen et al, 2001;Tani et al, 2003). The two-hybrid assay also revealed that γ-SNAP does not bind to at least to six of the SNAREs tested, including STX4 and STX18, although α-SNAP does bind to them .…”
Section: Introductionmentioning
confidence: 99%